SISTEM MONITORING KENAIKAN SUHU PADA TRANSFORMER BERBASIS IoT - Moh. Riyadh Dirga Pahlevi; Ardi Amir; Tan Suryani Sollu; Muh. Aristo Indrajaya (Foristek, 2021)
Transformers play an important role in generating electrical energy so that in maintaining their performance this transformer has a lot of protection so that the transformer can work as much as possible. Many things can interfere with transformers, namely when the transformer is overheated, a short circuit occurs, or is struck by lightning causing the transformer to burn, so a system that can provide fast, and extensive information is needed and is handled automatically by monitoring the temperature of the main transformer using a smartphone connected to the internet network. In this study, 2 DS18B20 sensors were used which were equipped with a Manual Call Point (MCP) as input and an ESP32 microcontroller module in which there was a Wi-Fi module as a data processor, then the output data would be sent via the internet to the Internet Of Things (IoT) platform for display. In the form of values, graphs, and notifications. The measurement results are in the form of temperature units in C which will be displayed via a smartphone using the Blynk IoT platform in the form of numbers and graphs in real-time according to the value detected by the sensor. Tests on sensors resulted in an average error of 3.29% on the Low side and 3.01% on the Upside.